Pigment epithelium-derived factor (PEDF) regulates metabolism and insulin secretion from a clonal rat pancreatic beta cell line BRIN-BD11 and mouse islets - Chen, Y.; Carlessi, Rodrigo; Walz, N.; Cruzat, Vinicius; Keane, Kevin; John, A.; Jiang, F.; Carnagarin, R.; Dass, C.; Newsholme, Philip (2016)
Pigment epithelium-derived factor (PEDF) is a multifunctional glycoprotein, associated with lipid catabolism and insulin resistance. In the present study, PEDF increased chronic and acute insulin secretion in a clonal rat ß-cell line BRIN-BD11, without alteration of glucose consumption. PEDF also stimulated insulin secretion from primary mouse islets. Seahorse flux analysis demonstrated that PEDF did not change mitochondrial respiration and glycolytic function. The cytosolic presence of the putative PEDF receptor - adipose triglyceride lipase (ATGL) - was identified, and ATGL associated stimulation of glycerol release was robustly enhanced by PEDF, while intracellular ATP levels increased. Addition of palmitate or ex vivo stimulation with inflammatory mediators induced ß-cell dysfunction, effects not altered by the addition of PEDF. In conclusion, PEDF increased insulin secretion in BRIN-BD11 and islet cells, but had no impact on glucose metabolism. Thus elevated lipolysis and enhanced fatty acid availability may impact insulin secretion following PEDF receptor (ATGL) stimulation.